2015 48th Hawaii International Conference on System Sciences 2015
DOI: 10.1109/hicss.2015.228
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Social Media on Organizational Socialization

Abstract: The purpose of this study is to investigate how an internal social media tool impacts new hire socialization. Using an interpretive case study of a financial services company, this study finds that social media use helped the new hires experience social acceptance, role clarity, self-efficacy, and knowledge of organizational culture. The social media system provided both socialization affordances and constraints. Both social bonding and social struggle were observed to result from the social media use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(70 citation statements)
references
References 20 publications
1
69
0
Order By: Relevance
“…Gonzalez et al . () found that social media use helped new hires gain social acceptance, role clarity, self‐efficacy, and understanding of organizational culture. However, Gonzalez et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonzalez et al . () found that social media use helped new hires gain social acceptance, role clarity, self‐efficacy, and understanding of organizational culture. However, Gonzalez et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Treem and Leonardi () suggested social media's essential roles in three broad organizational processes: workplace socialization, knowledge sharing, and power dynamics. Few studies have focused on social media use during organizational socialization (Gonzalez et al ., ), whereas studies on knowledge sharing via social media are abundant (Majchrzak et al ., ; Ellison et al ., ; Leonardi, ). Most studies focused on enterprise social media (ESM) that is designed for internal‐only communication within large corporations such as IBM, Microsoft, or HP (see Leonardi et al ., for a comprehensive review).…”
mentioning
confidence: 99%
“…Through the use of ESM, employees can build and extend their social relationships with colleagues, which creates a sense of community (Gonzalez et al, 2013). The blurring of boundaries between social life and work life shifts the work environment from one possibly defined by workplace isolation to one characterized by workplace integration or connectedness.…”
Section: Social Capital and Knowledge Sharingmentioning
confidence: 99%
“…We adapted the scale for ESM use from Gonzalez et al (2013), which research has shown to have high reliability and validity. We assessed workplace integration/isolation, which refers to an employee's perceived connectedness with / isolation from the company and colleagues and is shaped by support from colleagues and the opportunities to socialize and interact with others, using the scales by Marshall et al (2007) and Mulki and Jaramillo (2011).…”
Section: Measurement Instrumentmentioning
confidence: 99%
See 1 more Smart Citation